The Elasticity of Substitution and the Savings Ratio in the Neoclassical Theory of Growth - Ferguson, C. E. (Quarterly Journal of Economics, 1965)
I. Introduction, 465. — II. A neoclassical model of growth, 465. — III. The variable natural rate of growth, 466. — IV. Analysis of the variable path, 468. — V. Conclusion, 471.